Mobile application for wildlife capture–mark–recapture data collection and query. (23rd August 2013) - Bateman, Heather L.; Lindquist, Timothy E.; Whitehouse, Richard; Gonzalez, Maria M.
ABSTRACT Capture–mark–recapture (CMR) approaches are often used in the management and conservation of wildlife species and effective approaches to estimate populations rely on accurate data‐collection techniques. Unfortunately, sampling errors can arise at several steps in the CMR process. We designed and applied a mobile application (app) for field‐collected data from a CMR study on herpetofauna. Entering data into a digital format in the field using the mobile application eliminated timely steps to process handwritten data sheets and double‐checking data entries. Applications were developed for mobile devices on the iOS and Android operating systems. Both platforms have similar user interactions via data entry on a touch screen using pre‐programmed fields, checkboxes, drop‐down menus, and keypad entry. Our mobile application includes features to insure collection of all measurements in the field through pop‐up messages and can proof entries for valid formats. The application can assign unique numbers to newly captured individuals by querying the database for unused codes and eliminates the potential to assign 2 individuals with the same unique code. Technicians can query a database to view histories of previously captured animals from the field. During a 2‐month project, we estimated that using the mobile application instead of manual data entry and proofing via data sheets reduced our total project time by 10%. To our knowledge, this is the first application developed for mobile devices for biologists using CMR techniques and could be developed for use in other areas of field data collection. © 2013 The Wildlife Society.